Quantifying the degree of protection afforded by a no-take marine reserve on an exploited shark - da Silva, C; Kerwath, SE; Attwood, CG; Thorstad, EB; Cowley, PD; Økland, F; Wilke, CG; Næsje, TF (African journal of marine science, 2013)
Sharks have been shown to benefit from the protection of marine protected areas (MPAs). There is, however, little information on the degree of protection by MPAs to shark populations. The movements of individual smoothhound sharks Mustelus mustelus in, and adjacent to, a small (34 km 2 ) no-take MPA (Langebaan Lagoon Marine Protected Area; LMPA) situated on the west coast of South Africa were investigated over two years using acoustic telemetry. Sharks spent the majority of the time (in hours, average 79%) inside the reserve, and some sharks (n = 2 of 15 recorded during a full year) did not leave the reserve during the study period. Time spent inside the LMPA and the number of crossings of its boundary were strongly influenced by season. Sharks concentrated inside the LMPA during summer, whereas they were widely distributed throughout the study area during winter. Six sharks left the Saldanha Bay embayment during spring and winter for durations ranging from two to 156 days (median = 111 days). All returned to the bay within the study period. Individuals recorded over two years showed consistency in behavioural patterns and protection by the LMPA between years, and spent an average of 74% and 80% of the time inside the LMPA during the two study years respectively. The extended residency of smoothhound sharks within the LMPA suggests that no-take area protection may be a viable management option.